2017
DOI: 10.1016/j.urology.2017.07.048
|View full text |Cite
|
Sign up to set email alerts
|

Ten-year Mortality in Men With Nonmetastatic Prostate Cancer in Norway

Abstract: For all patients, the 10-year OM was about 3 times higher than PCSM, the greatest and lowest discrepancies emerging among patients with low- and high-risk tumors, respectively. The results support increased use of local treatment in high-risk patients. GGGs should be implemented in clinical practice. The role of ECOG performance status as prognostic factor has to be validated in future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 126 publications
(154 reference statements)
1
7
0
Order By: Relevance
“…Similarly, a previous population‐based study demonstrated reduced 10‐year relative survival in senior adults compared with younger men, with more pronounced differences in high‐risk patients 6 . Unlike previously reported, ECOG status was no longer an independent predictor of PCSM in senior adults when analyzed in a competing risk setting (Table 4, Table S3) 36 . Surprisingly, increasing ISUP grade groups were associated with higher risk of PCa death in younger than in senior men (Table 4).…”
Section: Discussionmentioning
confidence: 61%
“…Similarly, a previous population‐based study demonstrated reduced 10‐year relative survival in senior adults compared with younger men, with more pronounced differences in high‐risk patients 6 . Unlike previously reported, ECOG status was no longer an independent predictor of PCSM in senior adults when analyzed in a competing risk setting (Table 4, Table S3) 36 . Surprisingly, increasing ISUP grade groups were associated with higher risk of PCa death in younger than in senior men (Table 4).…”
Section: Discussionmentioning
confidence: 61%
“…All included studies (Table 1 ) were non-randomized studies, comprising of one prospective population-based cohort study [ 13 ], four retrospective population-based cohort studies [ 14 17 ], 10 single-institution retrospective cohort studies [ 18 27 ], two multicenter retrospective cohort studies [ 28 , 29 ] and two studies in which data for the two treatment groups came from different (institutional) databases [ 30 , 31 ]. Both cohort studies for which data were collected retrospectively from electronic medical records and studies that analyzed data from existing (institutional) databases were considered retrospective.…”
Section: Resultsmentioning
confidence: 99%
“…The number of included patients varied from approximately 100 to 40,000 and the median follow-up time ranged from approximately 3 to 10 years. Most studies ( n = 11) used the NCCN definition of high-risk PCa [ 15 17 , 21 27 , 29 ], two studies used the EAU definition [ 14 , 20 ] and in the remaining studies other definitions were used (e.g. Gleason score ≥ 8) [ 13 , 18 , 19 , 28 , 30 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…There may be several explanations for the lower 30-day mortality found in PCa patients after an AMI than in the general AMI population. Around 40% of nonmetastatic patients eligible for curative treatment in Norway have T1-localized disease [33]. This indicates that a significant number of patients diagnosed with localized disease are diagnosed as a consequence of PSA testing in asymptomatic men.…”
Section: Discussionmentioning
confidence: 99%